Altered Expression of Ion Channels in White Matter Lesions of Progressive Multiple Sclerosis: What Do We Know About Their Function? - Boscia, Francesca; Elkjaer, Maria Louise; Illes, Zsolt; Kukley, Maria (Frontiers in Cellular Neuroscience, 2021)
Despite significant advances in our understanding of the pathophysiology of multiple sclerosis (MS), knowledge about contribution of individual ion channels to axonal impairment and remyelination failure in progressive MS remains incomplete. Ion channel families play a fundamental role in maintaining white matter (WM) integrity and in regulating WM activities in axons, interstitial neurons, glia, and vascular cells. Recently, transcriptomic studies have considerably increased insight into the gene expression changes that occur in diverse WM lesions and the gene expression fingerprint of specific WM cells associated with secondary progressive MS. Here, we review the ion channel genes encoding K+, Ca2+, Na+, Cl- channels, ryanodine receptors, TRP channels, and others that are significantly and uniquely dysregulated in active, chronic active, inactive, remyelinating WM lesions, and normal-appearing WM of secondary progressive MS brain, based on recently published bulk and single nuclei RNA-sequencing datasets. We discuss the current state of knowledge about the corresponding ion channels, and their implication in the MS brain or in experimental models of MS. This comprehensive review suggests that the intense upregulation of voltage-gated Na+ channels genes in WM lesions with ongoing tissue damage may reflect the imbalance of Na+ homeostasis that is observed in progressive MS brain, while the upregulation of a large number of voltage-gated K+ channel genes may be linked to a protective response to limit neuronal excitability. In addition, the altered chloride homeostasis, revealed by the significant downregulation of voltage-gated Cl- channels in MS lesions, may contribute to an altered inhibitory neurotransmission and increased excitability.